The concept of modal choice of law rules - Hook, Maria (Journal of private international law, 2015)
This article conceptualises a widely used rule of the conflict of laws: the modal choice of law rule. Modal choice of law rules provide choice of law-specific ex ante regulation for choice of law elements. For example, a rule that provides that a choice of law agreement must be in writing is a modal choice of law rule. Choice of law elements may be subject to modal choice of law rules, substantive law or judicial discretion - or a mix of all three. The article unveils the different purposes served by modal choice of law rules. It demonstrates that modal choice of law rules are capable of importing both conflicts-related and substantive considerations into the choice of law process.